2019
DOI: 10.1016/j.celrep.2019.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Control of Intestinal Cell Fate by Dynamic Mitotic Spindle Repositioning Influences Epithelial Homeostasis and Longevity

Abstract: Highlights d Spindles reorient from oblique to planar during growth, driving symmetric outcomes d Stress-and aging-mediated activation of JNK promotes planar spindles d JNK interacts with Wdr62 and represses Kif1a expression to promote planar spindles d Restoring oblique spindles in old flies extends lifespan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 89 publications
(130 reference statements)
2
68
0
Order By: Relevance
“…Consistent with earlier reports (Hu and Jasper, 2019;Jin et al, 2017;O'Brien et al, 2011), approximately 23% of all clones were products of symmetric divisions in CR flies (Fig. 7J).…”
Section: Brevis Alters Progenitor Cell Identity and Promotes Symmesupporting
confidence: 93%
“…Consistent with earlier reports (Hu and Jasper, 2019;Jin et al, 2017;O'Brien et al, 2011), approximately 23% of all clones were products of symmetric divisions in CR flies (Fig. 7J).…”
Section: Brevis Alters Progenitor Cell Identity and Promotes Symmesupporting
confidence: 93%
“…Furthermore, differential Notch activities due to the Par complex activity induce distinct cellular differentiation pathways (Guo and Ohlstein, 2015). Recent work has also shown that the spindle orientation in ISCs is tightly linked with cell fate, where planar orientation gives rise to two ISCs and angular orientation generates a ISC-EB pair (Hu and Jasper, 2019). Here, through analyzing different mitotic phases of ISCs, separable old versus new H3 distribution are detectable in prophase and prometaphase ISCs, indicating that this asymmetry is intrinsically established prior to mitosis (Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Injury stimulus may impact the mode of regeneration, as symmetric ISC divisions are not reported to increase following P. entomophila infection (Jin et al, 2017). Related to this idea, ISC spindle orientation was recently tied to division outcome (symmetric versus asymmetric), and was shown to be differentially regulated by varying stress stimuli (Hu and Jasper, 2019). Importantly, the injured mouse gut is also capable of ISC-mediated regeneration (Barriga et al, 2017;Metcalfe et al, 2014;Yan et al, 2012).…”
Section: The Midgutmentioning
confidence: 99%